Oñati Proceedings: Official responses to problem juveniles: Some international reflections - García Ramos, José Ignacio (dir.) (1991)
Contiene: The decline in juvenile delinquency; A strategy for the cross-cultural study of juvenile justice; Dealing with juvenil de linquency: The re-education of the delinquent in the People's Republic of China; Canadian juvenile justice reform; Family empower ment in juvenile justice in New Zealand; Using reintegrative shaming effectively; Beyond punishment, surveillance and traditional treatment; The Juvenile Court of Cook County; Two strategies for defending juveniles in Australia.